Exposure–Response of Wheat Cultivars to TiO2 Nanoparticles in Contrasted Soils. Issue 2 (17th February 2019) - Zahra, Zahra; Ali, Muhammad Arif; Parveen, Amna; Kim, EunBi; Khokhar, Muhammad Fahim; Baig, Sofia; Hina, Kiran; Choi, Hyung-Kyoon; Arshad, Muhammad
ABSTRACT: Unprecedent usage of nanoparticles (NPs) over very large scale has raised concerns about their release into agro-environments. The effects of these emerging pollutants on staple food crops and contrasted soils are not very well documented. The main aim of present work was to investigate the exposure–response of 10 wheat cultivars to titanium dioxide (TiO2 ) NPs (0–1000 mg kg −1 ) in terms of early growth parameters followed by evaluation of the selected cultivar for complete growth cycle cultivated on contrasted soils in terms of various physicochemical characteristics. Among all the 10 tested wheat cultivars, only Galaxy cultivar sustained to the whole TiO2 NPs exposure range. TiO2 NPs exposure at 1000 mg kg −1 adversely affected the early growth response parameters in MH, Ujala, Uqab, Shafaq and FSD wheat cultivars which clearly indicated the toxic effects induced by NPs. Pot studies were performed using Galaxy cultivar cultivated in different textured soils (loam and sandy loam). At the highest tested concentration of TiO2 NPs, plant growth, biomass and phosphorus (P) concentration along with other tested parameters were not improved in both types of soils compared to their respective control groups. These results suggested the controlled use of NPs to avoid the NPs contamination in soil–plant ecosystems in the longer run.